2020
DOI: 10.1111/1365-2656.13381
|View full text |Cite
|
Sign up to set email alerts
|

Increased acclimation ability accompanies a thermal niche shift of a recent invasion

Abstract: Globalization is removing dispersal barriers for the establishment of invasive species and enabling their spread to novel climates. New thermal environments in the invaded range will be particularly challenging for ectotherms, as their metabolism directly depends on environmental temperature. However, we know little about the role climatic niche shifts play in the invasion process, and the underlining physiological mechanisms. We tested if a thermal niche shift accompanies an invasion, and if native and introd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 96 publications
3
14
0
Order By: Relevance
“…Notably, the latter difference is associated with a better ability to survive cold winters in Swedish compared to French core populations (Arambourou & Stoks, 2015), suggesting the difference in chill coma recovery time to be biologically significant. Also, in other study systems, increases in cold tolerance associated with range expansion have been observed (Bujan et al, 2020;Butin et al, 2005;Kolbe et al, 2014;Medley et al, 2019). Related to this, latitudinal differences in cold resistance (higher in highlatitude regions) is a general pattern described in other insects (e.g.…”
Section: Evolution Associated With the Range Expansion In The Edge Regionsupporting
confidence: 55%
“…Notably, the latter difference is associated with a better ability to survive cold winters in Swedish compared to French core populations (Arambourou & Stoks, 2015), suggesting the difference in chill coma recovery time to be biologically significant. Also, in other study systems, increases in cold tolerance associated with range expansion have been observed (Bujan et al, 2020;Butin et al, 2005;Kolbe et al, 2014;Medley et al, 2019). Related to this, latitudinal differences in cold resistance (higher in highlatitude regions) is a general pattern described in other insects (e.g.…”
Section: Evolution Associated With the Range Expansion In The Edge Regionsupporting
confidence: 55%
“…We also emphasise the tremendous acclimation potential displayed by ant species, which may allow them to cope with future changes in temperature. Some studies have found that invasive species can exhibit large shifts in both CT min and CT max , for example in Wasmannia auropunctata (Coulin et al ., 2019) and Tapinoma magnum (Bujan et al ., 2021), which can translate into modifications in thermal niches that facilitate invasiveness. Other research has characterised the acclimation capacities of ants, as shown for two Aphaenogaster species in temperate forests in the USA (Warren & Chick, 2013).…”
Section: Physiological Thermal Limits Species Distribution Ranges And...mentioning
confidence: 99%
“…The physiological traits that bracket such thermal performance curves are often defined as critical thermal limits and represent the range of temperatures at which an organism can be active. Critical thermal limits have been well‐explored in ectotherms with numerous studies focusing on diverse and abundant taxa such as ants (Baudier et al, 2018; Bishop et al, 2017; Braschler et al, 2020; Bujan et al, 2021; Garcia‐Robledo et al, 2018; Penick et al, 2017; Roeder, Bujan, et al, 2021). Questions linger through on how temperature affects different aspects of foraging and if activity is closely linked to an organism's thermal limits (Cerdá et al, 1998; Pereboom & Biesmeijer, 2003; Spicer et al, 2017; Welch et al, 2020).…”
Section: Introductionmentioning
confidence: 99%